2015
DOI: 10.1186/s12917-015-0326-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural Besnoitia besnoiti infections in cattle: hematological alterations and changes in serum chemistry and enzyme activities

Abstract: BackgroundThe emerging disease bovine besnoitiosis is caused by the apicomplexan parasite Besnoitia besnoiti. Clinical signs of acute besnoitiosis are pyrexia, anorexia and subcutaneous edema. In subacute and chronic besnoitiosis parasitic cysts arise in a variety of tissues and affected cattle display skin lesions and weight loss. In all stages of bovine besnoitiosis, lesions can be found in many organ systems and therefore presumably alter a variety of laboratory parameters. In this study, the impact of natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
(26 reference statements)
5
23
0
Order By: Relevance
“…Despite being a non‐specific lesion, target locations where vasculitis was found suggested that this might be a consequence of endothelial damage produced by the parasite during the acute phase. Similar lesions have been described under natural infection (Langenmayer et al., ). Focal degenerative lesions in testicle of the calves were observed only in relation to vasculitis that probably contributed to mild degenerative changes in the germinal epithelium.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Despite being a non‐specific lesion, target locations where vasculitis was found suggested that this might be a consequence of endothelial damage produced by the parasite during the acute phase. Similar lesions have been described under natural infection (Langenmayer et al., ). Focal degenerative lesions in testicle of the calves were observed only in relation to vasculitis that probably contributed to mild degenerative changes in the germinal epithelium.…”
Section: Discussionsupporting
confidence: 81%
“…However, the lesions observed in the reproductive tract were compatible with normal testicular function. Remarkably, in this study, a tissue cyst was located at the reticular dermis of the carpus region, a less frequent location than the papillary dermis (Langenmayer et al., ). As expected, a higher parasite intra‐organic distribution was found by PCR compared with histopathological results.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Of 33 new clinical and 12 new serological cases, only 6.7% (3/45) were observed by the owner with clinical signs consistent with acute bovine besnoitiosis (separation from the herd, nasal/ocular discharge). Two of these cases were included in a separate cohabitation trial (as Study animals 20 and 22), details of disease course were described elsewhere (Langenmayer, Scharr, Sauter‐Louis, Schares, & Gollnick, ). The remaining animal separated from the herd in summer 2009 (between HC2 and HC3), showed nasal and ocular discharge and seroconverted shortly after clinical signs receded.…”
Section: Resultsmentioning
confidence: 99%